Body mass index and serum lipid levels - Navarrete Mejía, Pedro Javier (2016)
Objective: To identify the association between the body mass index (BMI) and serum lipid levels in adult people. Material and Methods: Observational, transversal and retrospective study. Non experimental investigation design. The population was conformed for people treated in private health centers in Metropolitan Lima. The evaluations of the BMI and the laboratorial tests to know the seric concentration of lipids were taken between October 2014 and October 2015. It was determined the association between the BMI and the seric lipid levels using the Chi2 test. People with comorbidity that could modify the seric levels of lipids were excluded. Results: 39.7% of people studied were male and 60.3% were female. The average age was 34.2 years old. 40.7% (1227/3016) of population were obese and overweight. The results show a higher level of obesity or overweight in male people over female (54.6% and 33% respectively). 19.7% (594/3016) of the tested people presented high triglycerides seric levels. 27.9% (841/3016) presented high cholesterol levels and 38.8% (1146/3016) presented low cHDL levels. The cLDL levels and cVLDL levels were similar in both groups (male and female). Conclusions: The investigation determined the significant statistical association between the BMI and triglycerides (p < 0.05), cholesterol (p < 0.05) and cHDL (p < 0.05).